SCREENING OF ANTIGONORRHOEAL ACTIVITY OF SOME MEDICINAL PLANTS IN NEPAL - KESHAB CHANDRA MONDAL; DIPAK BHARGAVA; SANJAY KAR; JAGADISH NARAYAN SHIVAPURI; BIKASH SHAKYA; CHIRANJIT MAITY (International Journal of Pharma and Bio Sciences, 2011)
In view of the wide spread emergence of antibiotic resistant Neisseria gonorrhoeae isolates, the antigonococcal activity of ten Nepalese folk medicinal plants commonly used by the ethnic groups of peoples was evaluated. Among ten plant extracts, the ethanolic extracts of four plants and hexane extracts of one plant were very sensitive to N. gonorrhoeae. The maximum mean zone of inhibition by agar well diffusion method was seen for Eupatorium odoratum and the minimum was for Syzygium cumini. Similarly, the minimum inhibitory concentration by test tube dilution method for Eupatorium odoratum was the least followed by Ocimum sanctum, Sapindus mukorossi, Allium sativum and Syzygium cumini. Qualitative phytochemical analysis of the extracts reveals the presence of bioactive components. Thus, the result of this study justified the folkloric usage of the studied plants and concluded that these plants extract have great potential in finding new clinically effective antigonorrhoeal compounds.